Utilization of the ZIS Application: Alternative Communication Media for Qurban and Zakat Savings at the Arrahman Protanmas Mosque, Cianjur - Pupu Jamilah; Astri Dwi Andriani; Iis Kartini; Adi Kuncoro (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
The ZIS application is a digital solution used to facilitate the management of zakat, infaq and alms (ZIS) at the Arrahman Mosque. This application facilitates pilgrims in carrying out transactions easily and quickly, and provides transparent information regarding the collection and distribution of funds. By using technology, communication between mosque administrators and congregation becomes more efficient, thereby increasing community participation in qurban and zakat programs. This application also provides features that support education about the importance of zakat and sacrifice, helping to increase awareness and involvement of people in giving charity. It is hoped that the use of the ZIS application at the Arrahman Mosque can strengthen the sense of togetherness and social care among the congregation, as well as facilitate a more planned and structured worship process.